Activation of ERK1/2 and TNF-α production are regulated by calcium/calmodulin signaling pathway during Penicillium marneffei infection within human macrophages. (April 2016) - Chen, Renqiong; Ji, Guangquan; Wang, Ling; Ren, Hong; Xi, Liyan
Abstract: Previous study have shown that Penicillium marneffei ( P. marneffei )-induced TNF-α production via an extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase-dependent mechanism is an important host defence mechanism against P. marneffei in human macrophages. Therefore, we explore signaling pathway that regulates TNF-α secretion and activation of ERK1/2 by intracellular signaling mechanisms during P. marneffei infection. We found that ERK1/2 activation was dependent on the calcium/calmodulin/calmodulin kinase Ⅱ pathway in P. marneffei -infected human macrophages. In contrast, P. marneffei -induced p38 MAPK activation was negatively regulated by calcium/calmodulin/calmodulin kinase Ⅱ signaling pathway. Furthermore, TNF-α production in P. marneffei -infected human macrophages was also dependent on Ca 2+ /calmodulin/calmodulin kinase Ⅱ pathway. These data suggest that Ca 2+ /calmodulin/calmodulin kinase Ⅱ pathway plays vital regulatory roles in macrophage activation and subsequent cytokine production during P. marneffei infection. Highlights: Effect of Ca 2+ on activation of ERK1/2 in macrophages stimulated by P. marneffei . CaM is required for P. marneffei -induced activation of ERK1/2. Role of CaMKII in P. marneffei -induced activation of ERK1/2. Effect of the CaM/CaMKII pathway on TNF-α production.